Investigating the Role of Word Knowledge Components in Chinese L2 Writing Ability - Min, Changyong; Sukying, Apisak (Journal of language teaching, linguistics, and literature, 2024)
A body of research has looked into the nature of multiple-word knowledge components in recent years. However, the individual role of these components in L2 writing proficiency still remains unclear. The present study examined the interrelations between six-word knowledge components and explored the relationships between the lexical components and productive word use and L2 writing ability. The study adopted a multi-task approach using the word knowledge framework by Nation (2013, 2022) and the model of word knowledge components required in writing proposed by Coxhead (2007). Six measures, including one receptive word component (overall word size) and five productive depth knowledge components (productive form and meaning, association, productive derivation and collocation), were designed and validated to measure 147 Chinese EFL university learners' word knowledge relative to their word use and argumentative writing ability. The correlation and regression results demonstrated that derivative form production was the best predictor of word use and L2 writing ability. Its contribution was even stronger than productive form and meaning, though the latter two were also closely related to L2 writing and word use. Association and collocation predicted less variance yet still correlated with productive skills. However, the receptive size measured by the VLT had no correlations with L2 writing and lexical proficiency. Overall, this study provides empirical evidence for the theoretical word knowledge models and yields nuanced ideas regarding the smallest lexical predictors of L2 writing. Pedagogical implications for EFL vocabulary pedagogy are also discussed.